MED12-Related Disease in a Chinese Girl: Clinical Characteristics and Underlying Mechanism - Wang, Chao; Lin, Longlong; Xue, Yan; Wang, Yilin; Liu, Zhao; Ou, Zicheng; Wu, Shengnan; Lan, Xiaoping; Zhang, Yuanfeng; Yuan, Fang; Luo, Xiaona; Wang, Chunmei; et al. (Frontiers in Genetics, 2020)
MED12 is a member of the mediator complex, which plays a critical role in RNA transcription. Mutations in MED12 cause X-linked intellectual disability and other anomalies collectively grouped as MED12-related disorders. While MED12 mutations have been most commonly reported in male patients, we present the case of a 1-year-old girl with clinical characteristics similar to MED12-related disorders. To explore the clinical characteristics of the condition and its possible pathogenesis, we analyzed the patient’s clinical data; genetic testing by whole-exome sequencing revealed a de novo heterozygous mutation (c.1249-1G > C) in MED12. Further cDNA experiments revealed that the patient had an abnormal splicing at the skipping of exon9, which may have produced a truncated protein. qPCR showed decreased MED12 gene expression level in the patient, and an X-chromosome inactivation test confirmed a skewed inactivation of the X-chromosome. The lymphoblast transcription levels of the genes involved in the Gli3-dependent sonic hedgehog signaling pathway, namely CREB5, BMP4, and NEUROG2, were found to be significantly elevated compared with those of her parents and sex- and age-matched controls. Our results support the view that MED12 mutations may dysregulate the Sonic hedgehog (SHH) signaling pathway, which may have accounted for the aberrant craniofacial morphology of our patient.